Pengaruh Risk Capacity, Risk Tolerance, dan Risk Propensity pada Investment Priority dan Investment Strategy terhadap Investment Decision pada Gen-Z di Kota Samarinda - Rio Lauwindra; Yanuar Dananjaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the influence of Risk Capacity, Risk Tolerance, and Risk Propensity on Investment Priority and Investment Strategy, as well as the influence of Investment Priority and Investment Strategy on Investment Decision among Gen-Z in Samarinda. The research employs a quantitative approach, with the population consisting of Gen-Z individuals in Samarinda who have previously invested in stocks or cryptocurrency. A total of 207 respondents were obtained through the distribution of questionnaires to Gen-Z investors. Data analysis was conducted using SPSS software. The results indicate that all variables—Risk Capacity, Risk Tolerance, and Risk Propensity—have a significant influence on both Investment Priority and Investment Strategy. Furthermore, Investment Priority and Investment Strategy significantly affect Investment Decision among Gen-Z in Samarinda. The strongest influence on Investment Decision is attributed to Investment Strategy, while Risk Propensity demonstrates the greatest influence in shaping both Investment Priority and Investment Strategy.